Aging Potentiates Lateral but Not Local Inhibition of Orientation Processing in Primary Visual Cortex - Wang, Zhengchun; Yu, Shan; Fu, Yu; Tzvetanov, Tzvetomir; Zhou, Yifeng (Frontiers in Aging Neuroscience, 2018)
Aging-related declines in vision can decrease well-being of the elderly. Concerning early sensory changes as in the primary visual cortex, physiological and behavioral reports seem contradictory. Neurophysiological studies on orientation tuning properties suggested that neuronal changes might come from decreased cortical local inhibition. However, behavioral results either showed no clear deficits in orientation processing in older adults, or proposed stronger surround suppression. Through psychophysical experiments and computational modeling, we resolved these discrepancies by suggesting that lateral inhibition increased in older adults while neuronal orientation tuning widths, related to local inhibition, stayed globally intact across age. We confirmed this later result by re-analyzing published neurophysiological data, which showed no systematic tuning width changes, but instead displayed a higher neuronal noise with aging. These results suggest a stronger lateral inhibition and mixed effects on local inhibition during aging, revealing a more complex picture of age-related effects in the central visual system than people previously thought.